Effect of Volume Fraction Variation of Hybrid Composite Reinforced Bamboo Fiber and Fiber-Glass Using Polyyester Resin on Tensile Strength and Impack - Akbar Gultom; Ferri Safriwardy; Muhammad Nuzan Rizki; Masrullita Masrullita (Electronic Journal of Education, Social Economics and Technology, 2024)
The field of materials and technology has developed rapidly, various types of inventions have been developed and researched to obtain new materials that are suitable for use at low production costs. The potential of bamboo plants is promising where the availability is abundant and sustainable, the utilization of specimens is made with polyester binders reinforced with natural and synthetic fibers. The type of bamboo that will be investigated for the tensile strength and toughness of the specimen with the difference in fiber volume fraction is a reference for the combination of bamboo fiber and fiber-glass where the volume fraction of 25% SB:25% FG, 35% SB:15% FG and 40% SB:10% FG particles at a fixed resin volume is 50%. Of the three variations in the volume fraction, the highest tensile strength in a balanced fiber filler is 40% bamboo fiber: 10% fiber-glass with an average value of 80.907 MPa, with a tensile strain of 2.53 % The lowest tensile strength value is in the volume fraction of 35% bamboo fiber: 15% fiber-glass with an average value of 75.552 MPa, with a tensile strain of 2.09%. For the highest toughness value of the specimen is in the volume fraction of 35% bamboo fiber: 15% fiber-glass, i.e., 0.83 J〖/mm〗^2 With an absorbed energy of 43.73 joules. On the other hand, the lowest toughness value is in the volume fraction of 25% bamboo fiber: 25% fiber-glass with an average value of 0.24 J〖/mm〗^2. With an absorbed energy of 39.94 joules. The observation results showed that the fiber volume was good at a percentage of 40% SB with 15% FG suitable for combination as an alternative tensile material. The toughness value in the volume fraction of 40% SB:10% FG is very low. However, the observation of bamboo fiber fracture results has a strong enough ability for the application of manufacturing products and others.